Desarrollo de un sistema para la administración de los servicios de hospedaje y cafetería de La Casa del Café (2024)
This document describes the process that was carried out for the development of the web application for the administration of the lodging and cafeteria services of the Casa del Café. The information of these services was handled manually, therefore, it was possible that data could be lost or that a good record of the sales of the cafeteria could not be obtained. On the other hand, in the lodging area there was a manual registration of reservations, which did not allow control of the arrival of clients and the assignment of rooms.